An Analysis Of Multiple Choices Difficulty Level Made By Teacher Of Sma Negeri Saenam Kuanfatu - Chamelya Vivi Crystanty Sene; Mansuetus Mola; Timoteus Ajito (Departement of Mathematics Education, 2021)
This study attempts to ascertain the level of difficulty and quality of the English exam items created by SMA Negeri Saenam Kuanfatu teachers. The author employed a combination of mixed methods for data analysis. 40 multiple-choice test items and student answer sheets served as the instrument. 12 (30%) of the multiple-choice questions were classified as easy test items, 20 (50%) as moderate, and 8 (20%) as difficult items, according to the difficulty level analysis of the items using the formula suggested by Arikunto (2013). It can be concluded that the multiple choice test items were well reviewed from the difficulty level.